2003
DOI: 10.1093/dnares/10.4.137
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Structure of Gloeobacter violaceus PCC 7421, a Cyanobacterium that Lacks Thylakoids

Abstract: The nucleotide sequence of the entire genome of a cyanobacterium Gloeobacter violaceus PCC 7421 was determined. The genome of G. violaceus was a single circular chromosome 4,659,019 bp long with an average GC content of 62%. No plasmid was detected. The chromosome comprises 4430 potential protein-encoding genes, one set of rRNA genes, 45 tRNA genes representing 44 tRNA species and genes for tmRNA, B subunit of RNase P, SRP RNA and 6Sa RNA. Forty-one percent of the potential protein-encoding genes showed sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
188
1
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(204 citation statements)
references
References 30 publications
13
188
1
2
Order By: Relevance
“…The results obtained in this study strongly suggest that the slr1923 gene product of Synechocystis 6803 is Nakamura et al, 2003). The sequence alignment among the homologues indicated that Gll0878 has higher sequence similarity with other cyanobacterial counterparts.…”
Section: Phylogenetic Analysis Of Slr1923 Homologues and Their Distrisupporting
confidence: 56%
See 1 more Smart Citation
“…The results obtained in this study strongly suggest that the slr1923 gene product of Synechocystis 6803 is Nakamura et al, 2003). The sequence alignment among the homologues indicated that Gll0878 has higher sequence similarity with other cyanobacterial counterparts.…”
Section: Phylogenetic Analysis Of Slr1923 Homologues and Their Distrisupporting
confidence: 56%
“…PCC6803 (Synechocystis 6803; Kaneko et al, 1996), Anabaena sp. PCC7120 (Kaneko et al, 2001), Thermosynechococcus elongatus BP-1 (Nakamura et al, 2002), and Gloeobacter violaceus PCC7421 (Nakamura et al, 2003), or the unicellular red alga Cyanidiochyzan merolae 10D (Matsuzaki et al, 2004). Based on the fact that these organisms synthesize MV-chl(ide), it is reasonable to assume that there exists an 8-vinyl reductase gene(s) whose amino acid sequence is rather different from those found in higher plants or C. tepidum.…”
mentioning
confidence: 99%
“…WH8102 (Palenik et al, 2003), Prochlorococcus marinus MIT9313 (Rocap et al, 2003), P. marinus MED4 (Rocap et al, 2003), and P. marinus SS120 (Dufresne et al, 2003), as described by Mary and Vaulot (2003). Genes homologous to hik34 have also been found in the genomes of Gloeobacter violaceus PCC 7421 (Nakamura et al, 2003), Nostoc punctiforme (http://genome.jgi-psf. org/draft_microbes/nospu/nospu.home.html), and Trichodesmium erythraeum (http://genome.jgi-psf.org/ draft_ microbes/trier/trier.home.html).…”
Section: Orthologs Of Hik34 In Other Cyanobacteriamentioning
confidence: 96%
“…Although in many of the cyanobacterial genomes, such as in Synechococcus PCC 7002 and Anabaena PCC 7120, a petC gene family can be found, only the main petC gene, which is cotranscribed with petA, is present in the genomes of the thermophilic cyanobacterium Thermosynechococcus elongatus (39,40) and of the mesophilic cyanobacterium Gloeobacter violaceus PCC 7421 (41). Therefore, the occurrence of a petC gene family seems to be common but not obligatory in cyanobacteria.…”
Section: Presence Of Multiple Genes For Rieskementioning
confidence: 99%